Urban ornithology studies in Colombia: a literature review (2013)
This paper reviews what has been published in peer-reviewed journals about birds in Colombian cities, complementing an important Latin American review article that was recently published. This review identifies 55 papers dealing with 12 Colombian cities which exceeds by 50 the the number of studies previously considered. Species lists and Ecological Studies are the most frequent studies. Medellín is the city with the most studies (26 papers), whereas Bogotá (nine), Cali and Popayán (four each) had fewer publications. Although our review detects important publications not previously considered, we conclude that urban ornithology in Colombia is still in its infancy considering the duration, number, quality, impact and depth of studies so far published.